Respuesta :
The answer is:
______________________________________________________
[D]: (−∞, −2) ∪ (−2, 2) ∪ (2, ∞) ;
______________________________________________________
Note: We are given: f(x) = x / (x² + 4) ;
____________________________________________
Note that: (x² + 4) ; factors into: "(x + 2)(x − 2)"
_______________________________________________
So: f(x) = x / (x² + 4) ; ↔ f(x) = x / [(x + 2)(x − 2)] ;
_______________________________________________
and since one cannot divide by "0"; the "denominator" cannot equal "0";
so the "denominator", which is: "[(x + 2)(x − 2)]" ; cannot equal "0".
Since the "denominator" is the "product of two values", then "neither one nor both of the two values" can equal "0" ; since anything multiplied by "0" equals "0".
__________________
So, since the denominator = [(x + 2)(x − 2)] ;
______________________________________________
Start with:
__________
x + 2 = 0 ;
Subtract "2" from each side ;
x + 2 − 2 = 0 − 2 ;
_______________________
x = -2 ; So, x ≠ -2 ; because if x = -2, the denominator is 0.
__________________________________
Then;
_______________________
x − 2 = 0 ;
Add "2" to each side;
x − 2 + 2 = 0 + 2 ;
x = 2 ; So, x ≠ 2 ; because when if x = 2 , the denominator is "0".
_______________
So, x ≠ -2 ; because if x = -2, the denominator is 0.
x ≠ 2 ; because when if x = 2 , the denominator is "0".
x < -2 , x can be less than -2 ; but not equal to -2 .
x > 2 , x can be greater than 2; but not equal to 2.
-2 > x > 2 ; x can be between -2 and 2 ; but not equal to -2 or 2.
________________________________________________________
______________________________________________________
[D]: (−∞, −2) ∪ (−2, 2) ∪ (2, ∞) ;
______________________________________________________
Note: We are given: f(x) = x / (x² + 4) ;
____________________________________________
Note that: (x² + 4) ; factors into: "(x + 2)(x − 2)"
_______________________________________________
So: f(x) = x / (x² + 4) ; ↔ f(x) = x / [(x + 2)(x − 2)] ;
_______________________________________________
and since one cannot divide by "0"; the "denominator" cannot equal "0";
so the "denominator", which is: "[(x + 2)(x − 2)]" ; cannot equal "0".
Since the "denominator" is the "product of two values", then "neither one nor both of the two values" can equal "0" ; since anything multiplied by "0" equals "0".
__________________
So, since the denominator = [(x + 2)(x − 2)] ;
______________________________________________
Start with:
__________
x + 2 = 0 ;
Subtract "2" from each side ;
x + 2 − 2 = 0 − 2 ;
_______________________
x = -2 ; So, x ≠ -2 ; because if x = -2, the denominator is 0.
__________________________________
Then;
_______________________
x − 2 = 0 ;
Add "2" to each side;
x − 2 + 2 = 0 + 2 ;
x = 2 ; So, x ≠ 2 ; because when if x = 2 , the denominator is "0".
_______________
So, x ≠ -2 ; because if x = -2, the denominator is 0.
x ≠ 2 ; because when if x = 2 , the denominator is "0".
x < -2 , x can be less than -2 ; but not equal to -2 .
x > 2 , x can be greater than 2; but not equal to 2.
-2 > x > 2 ; x can be between -2 and 2 ; but not equal to -2 or 2.
________________________________________________________